2022
DOI: 10.3389/fcell.2022.797855
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stimulation Protects Against Chondrocyte Pyroptosis Through Irisin-Induced Suppression of PI3K/Akt/NF-κB Signal Pathway in Osteoarthritis

Abstract: Irisin, a myokine secreted by muscle during physical exercise, is known to have biological activities in different cell types. Chondrocyte inflammation and pyroptosis have been shown to play important roles in osteoarthritis (OA). In this study, we investigated the effects of exercise-induced irisin during different intensities of treadmill exercise in a rat OA model and the anti-inflammatory and antipyroptosis mechanism of irisin in OA chondrocytes. Forty-eight SD rats (n = 8) were randomly assigned to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 51 publications
(57 reference statements)
4
49
0
Order By: Relevance
“…The data detected by ELISA suggested that Tai Chi intervention for 12 weeks could significantly reduce the concentration of the serum inflammatory factors including ROS, NF-κB, NEK7, NLRP3, ASC, Caspase-1, GSDMD, IL-1β, and IL-18 in patients with pre-diabetes, indicating that Tai Chi intervention could relieve vascular and systemic inflammation. Another important finding of our study is that the level of irisin in the blood of patients with pre-diabetes increased slightly after 12 weeks of Tai Chi intervention (P<0.01) (as shown in Figure 1B ), which is consistent with the study of Jia ( 42 ). Therefore, 12 weeks of Tai Chi intervention can significantly decrease the expressions of NEK7, NLRP3, ASC, Caspase-1, GSDMD, IL-1β, and IL-18, while increasing the expression of irisin in pre-diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…The data detected by ELISA suggested that Tai Chi intervention for 12 weeks could significantly reduce the concentration of the serum inflammatory factors including ROS, NF-κB, NEK7, NLRP3, ASC, Caspase-1, GSDMD, IL-1β, and IL-18 in patients with pre-diabetes, indicating that Tai Chi intervention could relieve vascular and systemic inflammation. Another important finding of our study is that the level of irisin in the blood of patients with pre-diabetes increased slightly after 12 weeks of Tai Chi intervention (P<0.01) (as shown in Figure 1B ), which is consistent with the study of Jia ( 42 ). Therefore, 12 weeks of Tai Chi intervention can significantly decrease the expressions of NEK7, NLRP3, ASC, Caspase-1, GSDMD, IL-1β, and IL-18, while increasing the expression of irisin in pre-diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…There is increasing evidence that the NF-κB family plays a central role in the pro-inflammatory stress response of chondrocytes and controls their differentiation processes ( Marcu et al, 2010 ). Many studies have effectively reduced chondrocyte apoptosis and alleviated the symptoms of OA by inhibiting the NF-κB signaling pathway, making significant progress in researching potential therapeutic drugs for OA ( Zhu et al, 2021 ; Chen et al, 2022 ; Jia et al, 2022 ; Ni et al, 2022 ; Shi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 genes (CASP3, AKT1, HIF1A and IL10) were identified as candidate targets of Sal in both rattus norvegicus and homo sapiens. Recent studies have indicated that Akt/NF-κB and Caspase-3/GSDME pathways play a key role in regulating cell pyroptosis [ [31] , [32] , [33] , [34] ]. Western blot analysis was performed to measure the protein levels of Akt/NF-κB and Caspase-3/GSDME pathways-related genes.…”
Section: Resultsmentioning
confidence: 99%